The Santripreneur Vocational High School Entrepreneurship Education Management Model: A Single Case Study At Anharul Ulum Islamic Vocational High School In Blitar, East Java, Indonesia - Supriyono, Supriyono; Hidayaturrahman, Hidayaturrahman; Taufan Perdana Putra, Muhammad (International Journal of Science, Technology & Management, 2024)
The present study reports a single case study on the Santripreneur Entrepreneurship Education Management Model at An Harul Ulum Islamic Boarding School in Blitar, East Java, Indonesia. This study aimed to disclose the model of Santripreneur Entrepreneurship Education Management. The focuses of this study were (1)Planning in contexts of Policies, Programs, and program dissemination, (2) Organization in contexts of roles, responsibility, and procedures (3)Implementation in contexts of Method, Process, Legalities, Facilities, and Practices, and (4) Evaluation contexts of process and results. This study employed a qualitative embedded single case study. Data were collected through interviews, observation, and documentation. The data was analyzed by using the interactive analysis model. The results of the research revealed the following propositions :(1).Synchronization of the curriculum content and time frame enables the Santripreneur Entrepreneurship Educators to implement both the vocational and Pesantren-based Islamic studies, (2) The shared laboratory and teaching factory usage enables creative and productive teachers to effectively implement the Santripreneur Entrepreneurship Education, (3) The use of the internal quality assurance standard provides the trust of the customers., and (4). The Santripreneur Entrepreneurship Education results in the students. These propositions were generated from the Santripreneur Entrepreneurship Model consisting of the planning, organizing, implementation, and evaluation characterized by the pesantren-based education resulting in students’ entrepreneurial skills effectively.